Diffuse neuromatosis of intrahepatic and extrahepatic bile ducts as a rare cause of jaundice - Vassos, Nikolaos; Perrakis, Aristotelis; Schmid, Axel; Croner, Roland; Grützmann, Robert; Agaimy, Abbas (Visceral medicine, 2021)
Background: Neuroma of the biliary tree is extremely rare with no more than 100 cases reported so far. They mostly present with obstructive jaundice and have been commonly described after surgery or abdominal trauma. Although involvement of the extrahepatic bile duct is far more common, occurrence in the intrahepatic ducts has not so far been reported. Case Report: We describe 3 cases of diffuse biliary tree neuroma affecting 3 females aged 53-68 years. None had a history of neurofibromatosis type1. All presented with progressive obstructive jaundice with no evidence of gallstones. A history of previous surgery was noted in 2 patients. Initial impression on clinical and imaging examination was highly suspicious for bile duct carcinoma in 2 patients. Histology showed diffuse neuromatous proliferation replacing and thickening the bile duct walls. The third patient had concurrent neuroma and recurrent cholangiocarcinoma causing great clinical confusion as initial biopsy showed only benign neuroma, but CA 19-9 was steadily increasing, necessitating a second biopsy which then confirmed recurrent carcinoma. Conclusion: This uncommon cause of long-distance bile duct stenosis and progressive jaundice should be included in the differential diagnosis of bile duct neoplasms, in particular when there is a previous surgical history in this abdominal region.